Effect of Woven and Alkalization Treatment on Mechanical Properties of Kenaf Fibre Reinforced Polymer Composites - Wagiman, Abdullah; Shahzali, Mohd Shahrizad; Yahya, Mohd Sharir; Janon, Mohd Najib; Mustapa, Mohammmad Sukri; Hashim, Mohd Yussni (Multidisciplinary Applied Research and Innovation, 2020)
This paper report the effect of weave pattern and alkalization treatment on fabric kenaf fibre reinforced polymer matrix composite. Two types of yarn kenaf namely, non-treated and treated were prepared for the reinforcement. The yarns kenaf undergo alkalization treatment before the yarn woven into the fabric that based on plain and twill weave design. The matrix, a mixture of polyester and the catalyst of methyl ethyl ketone peroxide was infused into the fabric by using vacuum infusion system. Tensile test performed on the composite found that the weave design and the treatment give a significant impact on the tensile. Composite made from kenaf fabric which has low crimp percentage resulted in high tensile strength. Meanwhile, treatment performed on the yarn also improve the tensile strength of the composite.